Oral: Vaginal Misoprostol: Which route for induction of term labor? - Khatri (Adhikari), Ratna; Sharma, Jyoti; Amatya, Archana (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Aim: To compare the effectiveness of oral misoprostol with vaginal misoprostol for induction of labour at or more than 40 weeks of pregnancy. Method: Study design: Prospective comparative study. Duration: March 2005 to February 2006 (12 months)in the Dept of Obs/Gyn, TU Teaching Hospital, Kathmandu. Methods: Hundred nullipara (primi or gravida 2 with 1 spontaneous or induced abortion < 12 gestational weeks) in a singleton pregnancy > 40 but with Bishop's score < 4 were induced equally with either oral (100 mgm) Group A or vaginal (25mcg) Group B: were administered 4 hourly up to maximum of 6 doses. Primary outcome measures: duration of induction to active stage of labour or delivery, spontaneous rupture of membrane (SROM), meconium stained liquor (MSL), caesarean and neonatal morbidity with respect to Apgar score were assessed. Results: In vaginal 33 oral 17 had SROM with higher incidence of MSL (60% versus 12%) and higher caesarean 15%: 4%. Even there was > fetal distress 11/15: 2/7 group B/, which was statistically significant. No significant difference was noted in the pre induction cervical score, number of doses, induction to active stage of labour, induction to delivery time, use of oxytocin, failed induction and Apgar scores. Conclusion: Oral misoprostol found to be associated with less SROM, meconium stained liquor and vaginal birth and comparatively less neonatal care unit admissions outweighs its advantages over the vaginal misopristol, although either route were equally proven to be effective for inducing labour in women with unfavourable cervix (Bishop's score < 4) at term pregnancy. doi:10.3126/njog.v2i1.1472 N. J. Obstet. Gynaecol Vol. 2, No. 1, p. 23 - 28 May -June 2007